Coinfection by toxoplasma gondii and leishmania spp. in domestic cats (Felis catus) in State of Mato Grosso do Sul - Campos Braga, Audrey Renno; Ferreira Lopes Correa, Ana Paula [UNESP]; Camossi, Lucilene Granuzzio [UNESP]; Silva, Rodrigo Costa da [UNESP]; Langoni, Helio [UNESP]; Lucheis, Simone Baldini (Soc Brasileira Medicina Tropical, 2014)
Introduction: Leishmaniasis and toxoplasmosis are important to public health. Methods: Antibodies for Toxoplasma gondii and Leishmania spp. were evaluated in cats from Campo Grande, State of Mato Grosso do Sul, Brazil, a region endemic for canine visceral leishmaniasis. Serum samples from 50 asymptomatic cats were titrated for T. gondii by the immunofluorescence antibody test and modified agglutination test and for Leishmania spp. by the immunofluorescence antibody test. Results: These two agents coinfected two (4%) of the 50 tested animals. Conclusions: These findings demonstrate the concomitant presence of two important zoonoses in cats from Brazilian endemic regions for canine visceral leishmaniasis.
Keywords: Cats; Leishmania species; Toxoplasma gondii